QUALITY REVIEW OF DRIED SELAIS FISH (Kryptepterus lais) WITH ADDITION OF CHITOSAN SOLUTION DURING ROOM TEMPERATURE STORAGE - Setiyanto, Wahyu Pajar; Buchari, Dewita; Loekman, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this research was to review the quality of dried selais fish (Kryptopterus lais) by soaking of chitosan solution during room temperature storage. The methode used in this reseach was experimental methode by soaking of dried selais fish (Kryptopterus lais) with 3 % of chitosan solution concentration for 30 minutes of soaking time (K1) and without soaking of chitosan solution (K0), during 0, 7, 14 days of room temperature storage. The parameters tested were Total Plate Count, organoleptic analysis (appearance, aroma, texture) and chemical analysis. The result showed that the treatment was significant different to the quality of dried selais fish (Kryptopterus lais) during room temperature storage. The K1 treatment tend to have higher average than K0 treatment for all of parameters tested (Total Plate Count, organoleptic analysis (appearance, aroma, texture), and chemical analysis.Keywords : Chitosan, Kryptopterus lais, Quality